2021
DOI: 10.47836/pjtas.44.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Reproductive Performance of the Indigenous Kedah-Kelantan (KK) Cattle: A Review

Abstract: Kedah-Kelantan (KK) cattle plays a significant role for beef industry in Malaysia. KK cattle is a well-adapted local breed reared by traditional farming system with low quality feeds. KK cows normally produce a calf per year, which attracts farmers for commercial production. Currently, KK cattle is playing an important role for profitable beef production in Malaysia since the imported exotic breeds, crossbreds, and synthetic breeds of cattle could not perform to their full potential for sustainability of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…In this study, the mean body weights were 98.1 and 111.9 kg for KK and KK × Brangus bulls, respectively at 13 months with no significant difference (p˃0.05). This finding is in close agreement with the results of (Ariff et al, 1993;Islam et al, 2021) who reported the mean body weight in KK males as 102.3 and 100.5kg, respectively. Although, the results of this experiment is higher than results of Hafiz et al (2009) who reported 87.5 kg and comparatively lower than Johari and Jasmi (2009) who found 130kg in KK bulls at the same age.…”
Section: Prediction Of Body Weight Performancesupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, the mean body weights were 98.1 and 111.9 kg for KK and KK × Brangus bulls, respectively at 13 months with no significant difference (p˃0.05). This finding is in close agreement with the results of (Ariff et al, 1993;Islam et al, 2021) who reported the mean body weight in KK males as 102.3 and 100.5kg, respectively. Although, the results of this experiment is higher than results of Hafiz et al (2009) who reported 87.5 kg and comparatively lower than Johari and Jasmi (2009) who found 130kg in KK bulls at the same age.…”
Section: Prediction Of Body Weight Performancesupporting
confidence: 93%
“…Contrariwise, the ADGs from 13 to age at puberty were 0.35±0.1kg and 0.27±0.1 kg/d for KK × Brangus bulls and KK bulls, respectively with significant (p˂0.05) difference between groups. Islam et al (2021) reported almost similar findings (0.3kg/d) through meta-data analysis of average daily gain of KK reported by different researchers in different periods. There were also no significant (p˂0.05) differences of ADG between KK and KK × Brangus bulls for 19 to 24-months, 25 to 30-months and 13-months to age at maturity.…”
Section: Prediction Of Body Weight Performancesupporting
confidence: 74%
See 2 more Smart Citations
“…Government has taken an initiative to improve the meat production by importing more than 15 exotic breeds such as Charolais, Brahman, Brangus and Hereford breeds as purebreds and also for crossbreeding. These breeds especially Charolais have become a choice for crossbreeding to local breed which is Kedah-Kelantan (KK) because they have higher growth rate and body weight (Islam et al 2021). This mixed breed is locally known as Lembu Sado.…”
Section: Introductionmentioning
confidence: 99%